The Utilization of Idle Money on Mosque in Indonesia - Eddy Suratman; Gun Mayudi (International Journal of Zakat, 2025)
Islam is the fastest-growing religion in the world. With this growth, many new mosques have emerged, but their financial and social performance has not necessarily kept pace. Nowadays, many mosques prioritize saving money for construction and restoration, even when the mosque has already been completed. Moreover, there are many poor people living in the surrounding areas of these mosques. This implies that mosques often lack effective financial management and do not provide the expected spiritual, social, and economic benefits to their communities. This study finds opportunities and potentials of idle money amounting to IDR 1 trillion per month or approximately IDR 12 trillion per year in Indonesian mosques. Some factors that affect the presence of idle money in mosques are: ongoing or planned mosque restoration projects, the absence of clear work programs, a prevailing belief that a mosque’s success is measured by the size of its savings, and the tendency to save for future operational or emergency needs.